CALCULATION OF OXYGEN ISOTOPE FRACTIONATION IN MAGMATIC ROCKS - Zhao Z.-F.; Zheng Y.-F. (My University, 2002)
The increment method is applied to calculation of oxygen isotope fractionation factors for common magmatic rocks. The 18O-enrichment degree of the different compositions of magmatic rocks is evaluated by the oxygen isotope indices of both CIPW normative minerals and normalized chemical composition. The consistent results are obtained from the two approaches, pointing to negligible oxygen isotope fractionation between rock and melt of the same compositions. The present calculations verify the following sequence of 18O-enrichment in the magmatic rocks: felsic rocks>intermediate rocks>mafic rocks>ultramafic rocks. Two sets of internally consistent fractionation factors are acquired for phenocryst–lava systems at the temperatures above 1000 K and rock–water systems in the temperatures range of 0–1200 °C, respectively. The present calculations are consistent with existing data from experiments and/or empirical calibrations. The obtained results can be used to quantitatively determine the history of water–rock interaction and to serve geological thermometry for various types of magmatic rocks (especially extrusive rocks).